Enjoying the Heat? Co-Creation of Stakeholder Benefits and Sustainable Energy Development within Projects in the Geothermal Sector - David Cook; Ingibjörg Karlsdóttir; Inga Minelgaite (Energies, 2022)
Analysis of the sustainability implications of the geothermal industry has tended to take a high-level or systemic overview of national performance rather than deeper, stakeholder-focused investigations. This study seeks to begin to fill this gap in the literature, investigating the following research question: how do projects in the Icelandic geothermal energy sector create co-benefits with stakeholders and reflect the integration of sustainable energy development (SED)? The focus of the analysis is identifying the stakeholders, what the sustainability benefits co-created with stakeholders are, and when in the projects’ life-cycle do these occur. Based on eleven semi-structured interviews with project managers in Iceland’s geothermal industry, the study identifies an array of stakeholders in the sector, including national and municipal governments, public sector institutions, businesses, the public, employees, and landowners. The sustainability co-benefits of Iceland’s geothermal power projects are broad and cut across all six aspects of SED and multiple phases of the project life-cycle. Although the sustainability benefits are apparent, trade-offs are reported between pursuing an economically efficient energy system and nature conservation. This relates to unsustainable utilization of the resources and the environmental externalities of power production and consumption. Efforts to mitigate these effects are ongoing, and further pursuit of SED is likely in Iceland given its recognition within the nation’s new energy policy and to meet ambitious greenhouse gas emissions reduction targets in the government’s climate action plan. These are prominent issues in other nations seeking to decarbonize energy systems through increased utilization of geothermal resources.